Transformational Leadership of Principals in Improving Elementary School Teacher Performance - Hedi Mulyadi; Ida Tejawiani (Journal of Science and Education (JSE), 2026)
This research is motivated by the performance of teachers who have not met expectations not only in delivering subjects, but also in shaping students with good personalities and skills. One way to improve teacher performance is through effective principal leadership. This study aims to describe and analyze the transformational leadership of principals in improving teacher performance at SDN Mekarjaya and SDN Cinerang 2. The focus of this study is on four main indicators of transformational leadership: charisma, inspirational motivation, intellectual stimulation, and individual attention. This research is based on the transformational leadership theory proposed by Bass and Avolio. Transformational leadership focuses on developing the potential of subordinates through an inspiring and motivating approach. Principals who implement this leadership style are believed to create a conducive work environment, inspire teachers to improve their performance, and support their professional development. This study employed a qualitative descriptive approach. Data were collected through observation, in-depth interviews with principals and teachers, and document review relevant to teacher performance. The results of the study indicate that the transformational leadership of the principal in both locations successfully improved teacher performance. Principals who adopted this leadership style were able to create an environment that supported creativity, innovation, and cooperation among teachers. Teachers felt more motivated and received support in the development of learning and evaluation. Effective communication and individual attention from the principal also contributed significantly to improving teacher performance. The transformational leadership of the principal had a significant influence on improving teacher performance. The conclusion of this study is that the principal has successfully prioritized inspirational motivation, intellectual stimulation, and individual attention, the principal has succeeded in creating a conducive atmosphere for teacher professional development.